Influence of Farmers Human Resources Quality and Group Conditions on Simantri Application Level in Bali - I Gusti Agus Maha Putra Sanjaya; Nyoman Suparta (Warmadewa University Press, 2018)
Simantri is a regional government program started in 2009 which is one of the solutions to overcome the limitation of agricultural land as a result of land conversion and to improvement the farmers income in Bali. The aims of this research were to analyze the condition of Simantri application level in Bali, and also the influence of farmers human resources quality and the Simantri group condition on the application of cattle breeding, food crops, and cattle waste processing. Structured questionaires were used to obtain information from 138 respondents consisting of chairmans, secretaries, and treasurers of forty-six groups of Simantri from 2009-2010. The groups of Simantri selected by purposive sampling method. Data obtained were analyzed by descriptive method and statistic analysis. Results indicated that on average the Simantri application level classified very high. When viewed from three types of main Simantri activities, it turns out the application level of cattle waste processing on average is classified as moderate. The farmers human resources quality has proved has a positive and significant impact on the application of cattle breeding, food crops, and cattle waste processing. The Simantri group condition statistically has positive but not significant effect on the application of cattle breeding, food crops, and cattle waste processing. Keywords: Application Level, Integrated Farming System, Simantri,